To Get Rich is Glorious: Examining China’s Purpose of Wealth and its Implications for Indonesia - Widodo, Sarah Fitriani (Jurist-Diction, 2024)
AbstractThis essay examines the impact of Deng Xiaoping’s “To Get Rich is Glorious” concept on China’s economic reforms and its subsequent influence especially in Indonesia. Originating in the late 1970s, this concept spurred economic growth, entrepreneurship, and international engagement in China. The analysis delves into the historical aspects and current economic connections between China and Indonesia. It unveils China’s substantial contribution to Indonesia’s progress in infrastructure, development, digitalization, and industrialization. While bilateral relations present opportunities, challenges such as Indonesia’s reliance on Chinese debt and diplomatic issues are acknowledged. Future outlooks underscore the importance of ongoing collaboration to foster Indonesia’s economic growth, all within the framework of its partnership with China. In essence, Deng’s concept has not just influenced China’s course, but has also left a lasting impact on Indonesia’s economic path. Keywords: Deng Xiaoping; Economic Reforms; To Get Rich is Glorious.